Health care services for survivors of gender-based violence: a community and clinic-based intervention in Zambézia province, Mozambique. Issue 1 (2nd January 2023) - De Schacht, Caroline; Paulo, Paula; Van Rompaey, Sara; Graves, Erin; Prigmore, Heather L.; Bravo, Magdalena; Melo, Francisco; Malinha, João Eduardo; Correia, Della; Cossa, Raquel; Chele, Elsa; Audet, Carolyn
ABSTRACT: Mozambique introduced guidelines for integrated gender-based violence (GBV) services in 2012. In 2017, we trained providers on empathetic and supportive services to GBV survivors and introduced home-based services for survivors who are loss-to-follow up. Rate ratios of clinic visits were compared before and after intervention initiation, using exact significance tests. Data of 1, 806 GBV survivors were reviewed, with a total of 2005 events. The median age was 23 years (IQR 17–30) and 89% were women. Among those reporting violence, 69% reported physical violence, 18% reported sexual violence (SV), and 12% reported psychological violence. Rates of care-seeking behavior were higher in the intervention period (rate ratio 1.31 [95%CI: 1.18–1.46]); p < 0.01. Among those eligible for post-exposure prophylaxis (PEP), 94% initiated PEP. Uptake of HIV retesting improved in percentage points by 34% (14% to 48%), 34% (8% to 42%) and 26% (5% to 31%) at 1-, 3- and 6-months, respectively. The intervention led to an increase in the rate of GBV survivors seeking health care services, and improved rates of follow-up care among SV survivors initiating PEP. Strengthening of PEP adherence counseling remains crucial for improving GBV services.